STRATEGI PEMASARAM DALAM MENINGKATKAN PENJUALAN KELAPA DI KABUPATEN JEMBRANA - Nurul Khalifa Al Hadi; Nyoman Utari Vipriyanti; Nyoman Yudiarini; Cening Kardi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
Coconut is a strategic commodity that has a social, cultural and economic role in the life of the Indonesian people. The benefits of coconut plants lie not only in the flesh of the fruit which can be processed into coconut milk, copra, and coconut oil. The aims of this study were (1) to identify internal and external factors in increasing coconut sales in Jembrana Regency. (2) Formulating a strategy to increase coconut sales in Jembrana Regency. The marketing mix strategy includes the 4Ps, namely product, price, place, promotion. Respondents who became informants in this study amounted to 15 people. The analytical method in this study uses SWOT analysis. The results showed that the strength factors were high production, easy to get seeds, own coconut land, easy to cultivate, land fertility which was very suitable for coconut, and weakness factors were marketing promotion was still very weak, joint marketing network was weak, coconut cultivation locations were far away. from the city, the application of technology is less, capital is limited. Opportunity factors are increasing consumer purchasing power, consumer perceptions of the high benefits of coconuts, support from the Regency Government and the development of demand for fresh coconuts for the beverage and food industry. Threat factors are inter-production competitors, higher consumer bargaining positions, unstable selling prices, climatic or weather conditions